Parallelizing MCP-Haskell for Evaluating Haskell# Parallel Programming Environment - Carvalho Jr., F. H.; Lins, R. D.; Lima, R. M. F. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2001: Anais do XIII Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.2001.22209, 2001)
In this paper, we present the parallelization of a sequential functional implementation of a Monte Carlo Transport Problem, called MCP-Haskell[Hammes et al., 1995], using Haskell#. This experiment gave us important feedback for evaluating Haskel# features, helping us to answer some questions, like how expressive is Haskel# for representing known parallel computational patterns, how easy it is to build large scale parallel programs in an elegant and concise way, and how efficient are Haskell# programs. Based on our conclusions, we suggest new features to be incorporated in Haskel# to improve its expressiveness and performance. We also present the performance figures for the MCP-Haskell# benchmark.